Harnessing Opportunities for Productivity Enhancement for Sorghum & Millets (HOPE): Baseline Survey, Tanzania - Shipmann, Christin; Orr, Alastair; Muange, Elijah; Mafuru, January (ICRISAT, 2013)
The baseline survey was made in Singida Rural and Kondoa districts of Central Tanzania. A random sample of 360 farm households was sampled, divided into treatment, diffusion, and control groups. The survey was conducted in late 2010 and the results refer to the 2009-2010 agricultural year. A table with key quantitative findings is provided at the end of this summary.
Keywords: Baseline Survey Dryland Cereals